Occurrence of Portal Hypertension and Its Clinical Course in Patients With Molecularly Confirmed Autosomal Recessive Polycystic Kidney Disease (ARPKD) - Wicher, Dorota; Grenda, Ryszard; Teisseyre, Mikołaj; Szymczak, Marek; Halat-Wolska, Paulina; Jurkiewicz, Dorota; Liebau, Max Christoph; Ciara, Elżbieta; Rydzanicz, Małgorzata; Kosińska, Joanna; Chrzanowska, Krystyna; Jankowska, Irena (Frontiers in Pediatrics, 2020)
Purpose: Liver involvement in autosomal recessive polycystic kidney disease (ARPKD) leads to the development of portal hypertension and its complications. The aim of this study was to analyze the occurrence of the portal hypertension and its clinical course and the dynamics in patients with molecularly confirmed ARPKD in a large Polish center. Moreover, the available options in diagnostics, prevention and management of portal hypertension in ARPKD will be discussed. Materials and Methods: The study group consisted of 17 patients aged 2.5-42 years. All patients had ARPKD diagnosis confirmed by molecular tests. Retrospective analysis included laboratory tests, ultrasound and endoscopic examinations, transient elastography and clinical evaluation. Results: Any symptom of portal hypertension was established in 71% of patients. Hypersplenism, splenomegaly, decreased portal flow and esophageal varices were found in 47%, 59%, 56% and 92% of patients, respectively. Gastrointestinal bleeding occurred in 4 of 17 patients. Endoscopic variceal ligation (EVL) was performed at least once in 9 patients with esophageal varices. Conclusions: Portal hypertension and its complications are present in a significant percentage of ARPKD patients. They should be under the care of multidisciplinary nephrology-gastroenterology/hepatology team. Complications of portal hypertension may occur early in life. Endoscopic methods of preventing gastroesophageal bleeding, such as endoscopic variceal ligation, are effective and surgical techniques, including liver transplantation, are required rarely.